2009
DOI: 10.1080/01919510902841218
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production of Ozone and/or Microwave-Pretreated Canned Maize Production Sludge

Abstract: The production of canned maize is accompanied by formation of large volumes of waste water, with high contents of starch, and high chemical-and biochemical oxygen demand. In our work the effects of acidic, microwave and ozone pretreatment on the biogas production and aerobic biodegradability of canned maize production sludge were examined and the energy balance of the processes were determined when different sludge pretreatments were used. It was found that ozone treatment decreased the chemical oxygen demand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…During the mechanical pre-treatment of the sludge, the microbial cell wall is disrupted by shear stress or by sonication (Bougrier et al, 2006;Müller et al, 1998;Weemaes and Verstreate, 1998;Zhu and Beland, 2006). The chemical, thermo-chemical and oxidation treatments are also suitable for disintegrating of sludge, resulting increased solubilization efficiency and enhanced degradation of the macromolecules to low molecular-weight compounds (Beszédes et al, 2009;Park et al, 2004). Thermal treatments and its combination with alkaline or acidic treatment are widely used in sludge management.…”
Section: Introductionmentioning
confidence: 99%
“…During the mechanical pre-treatment of the sludge, the microbial cell wall is disrupted by shear stress or by sonication (Bougrier et al, 2006;Müller et al, 1998;Weemaes and Verstreate, 1998;Zhu and Beland, 2006). The chemical, thermo-chemical and oxidation treatments are also suitable for disintegrating of sludge, resulting increased solubilization efficiency and enhanced degradation of the macromolecules to low molecular-weight compounds (Beszédes et al, 2009;Park et al, 2004). Thermal treatments and its combination with alkaline or acidic treatment are widely used in sludge management.…”
Section: Introductionmentioning
confidence: 99%
“…This will improve the hydrolysis of the organic matter, accelerate the AD process, increase the biogas production, as well as reduce the digestion time and the amount of final residuals (Beszédes et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…After comparing acidic, microwave and ozone pretreatment on canned maize production sludge, Beszédes et al (2009) found that the combined pretreatment process with microwave and ozone could achieve higher biodegradability than single ozone treatment. However, it was also observed that MWI alone had no effect on biogas production.…”
Section: Microwave-ozone Pretreatmentmentioning
confidence: 98%